Frequency-Tunable Electromagnetic Absorber by Mechanically Controlling Substrate Thickness - Heijun Jeong; Manos M. Tentzeris; Sungjoon Lim (International Journal of Antennas and Propagation)
In this paper, we propose a frequency-tunable electromagnetic absorber that uses the mechanical control of substrate thickness. The absorption frequency of the proposed absorber can be changed by varying the substrate thickness. In order to mechanically control the substrate thickness, we introduce a 3D-printed molding with air space. The proposed structure consists of two layers and one frame: the FR4 substrate, polylactic acid (PLA) frame, and air substrate. The FR4 and PLA thicknesses are fixed, and the air thickness is varied using the PLA frame. Therefore, the effective dielectric constant of the overall substrate can be changed. The metallic rectangular patch and ground are patterned on the top and bottom FR4 substrates, respectively. The performance of the proposed tunable absorber is demonstrated from full-wave simulation and measurements. When both of the FR4 substrate thicknesses are 0.3 mm and the air thickness is changed from 1 to 3.5 mm, the absorption frequency is changed from 8.9 to 8.0 GHz, respectively. Therefore, the frequency-tuning capability of the proposed absorber is successfully demonstrated.